Allocation of economic costs in trigeneration systems at variable load conditions including renewable energy sources and thermal energy storage. (15th May 2018) - Pina, Eduardo A.; Lozano, Miguel A.; Serra, Luis M.
Abstract: As energy systems become more and more complex, the issue of the appropriate way to allocate the cost of the resources consumed increases because the way in which allocation is made directly affects the prices of the products obtained and, thus, the consumers' behavior. Thermoeconomics has been used to explain the cost formation process in complex energy systems. The thermoeconomic analysis of a trigeneration system including renewable energy sources (RES) and thermal energy storage (TES) was developed to determine the energy, capital, and total unit costs of the internal flows and final products. This work addresses issues not yet deeply studied in thermoeconomics, namely the joint production of energy services in dynamic energy systems and the incorporation of TES, RES (photovoltaic panels) and a component with different products for each operation mode (heat pump producing heat in heating mode and cooling in cooling mode). The interconnection between charging and discharging periods through the TES units was explored, allowing the discharged flow to be traced back to its production period. The trigeneration system resulted more profitable than the reference system, with total cost savings of 9942 €/yr, which was translated into the lower annual total unit costs of the final products. Highlights: The thermoeconomic analysis of a trigeneration system is performed. Novel capital cost allocation approach for the thermal energy storage is proposed. The energy, capital and total unit costs are determined for all energy flows. The unit costs are assessed on an hourly, monthly and annual basis. The total unit costs obtained are lower than the reference costs adopted herein.